Factors determining knowledge assets and processes. Selected problems of organizational learning of public organizations - Możdżeń, Michał; Chrabąszcz, Robert (Journal of Public Governance, 2012)
The article has been developed on the basis of an organizational learning model, created as a combination of the analysis of knowledge assets and processes, and of a list of organizational barriers working against effective learning within public organizations. The authors also use the results of a detailed study of the phenomenon of organizational learning in the public sector, conducted in 2011 as a part of the project “Learning Ministries”. The survey was conducted among the employees of Polish ministries. The aim of the article is to identify a set of fundamental factors influencing the processes of accumulating and using knowledge by the public sector. The authors also assess - in the framework of two theoretical dimensions that are divided into five empirical dimensions - the influence of the identified factors on the above-mentioned processes. Th e research methodology is based on factor analysis (Principal Component Analysis – PCA) conducted in order to identify the factors that describe knowledge assets and processes, and the dimensions of barriers for organizational learning. The next step consists in conducting a linear regression analysis (Ordinary Least Squares method – OLS) to identify the most important properties affecting knowledge assets and processes. The results show that there is a clear relationship between the dimensions of organizational learning and organizational culture, the characteristics of leaders and employees, as well as relations with the external environment and organizational flexibility.